Design of a dual band printed dipole antenna for WIFI application - Abdul Malek, Norun; Karsin, Siti Azwanie; Mohamad, Sarah Yasmin; Mohd. Isa, Farah Nadia; Asnawi, Ani Liza; Mohd. Ramly, Athirah (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2017)
Simulation and measurement of 2.4 GHz dipole antennas with baluns are presented and discussed. The design was made to study the characteristics of a dipole antenna before converting its configuration from wire to printed configuration. As a wire dipole antenna is prone to break, a printed dipole antenna with integrated via-hole balun printed on FR-4, Rogers TMM 4, and Rogers RT6002 substrates are presented. The study also focuses on improvement from a single band printed dipole antenna by adding another resonance frequency making it dual band. The simulated printed dipole antenna was made to resonate at 2.4 GHz and 5 GHz. Simulation was performed using CST Microwave Studio (CST MWS) to analyze the antenna performance. The proposed designs on RT6002 have the best return loss values of 13.2dB and 23.4dB with bandwidth of 17.2% and 33.9% respectively. Fabrication on Rogers RT6002 was selected for both single and dual band antenna. Measurements taken are in good agreement with the simulated results. From the results, it is demonstrated that the proposed antenna can be used for dual band Wi-Fi applications.